Current Uncertainties and Future Challenges Regarding NAD+ Boosting Strategies - Borut Poljšak; Vito Kovač; Irina Milisav (MDPI AG, 2022)
Precursors of nicotinamide adenine dinucleotide (NAD+), modulators of enzymes of the NAD+ biosynthesis pathways and inhibitors of NAD+ consuming enzymes, are the main boosters of NAD+. Increasing public awareness and interest in anti-ageing strategies and health-promoting lifestyles have grown the interest in the use of NAD+ boosters as dietary supplements, both in scientific circles and among the general population. Here, we discuss the current trends in NAD+ precursor usage as well as the uncertainties in dosage, timing, safety, and side effects. There are many unknowns regarding pharmacokinetics and pharmacodynamics, particularly bioavailability, metabolism, and tissue specificity of NAD+ boosters. Given the lack of long-term safety studies, there is a need for more clinical trials to determine the proper dose of NAD+ boosters and treatment duration for aging prevention and as disease therapy. Further research will also need to address the long-term consequences of increased NAD+ and the best approaches and combinations to increase NAD+ levels. The answers to the above questions will contribute to the more efficient and safer use of NAD+ boosters.